PENERAPAN MODEL PROBLEM BASED INTODUCTION PADA TEMA INDAHNYA KERAGAMAN BUDAYA NEGERIKU DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 42 PIDIE - Nia Wardhani (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
This study aims to determine the application of the Problem Based Introduction (PBI) model on the theme of the beauty of my country's cultural diversity in improving the learning outcomes of fourth grade students of MIN 42 Pidie. The type of this research is Classroom Action Research with the research subjects are students of class IV MIN 42 Pidie, totaling 19 students. This research was conducted in three cycles using observation, interview, test, field notes and documentation techniques. In the first cycle the average score obtained by students is 41.57 with classical completeness 15.78%, in the second cycle the average score obtained by students is 52.10 with classical completeness 42.10%, and in the third cycle the average value is an average of 83.68 with a classical completeness of 89.47%. Thus, it can be concluded that the application of the Problem Based Introduction (PBI) Model on the Theme of the Beauty of Cultural Diversity in my Country can Improve the Learning Outcomes of Class IV Students of MIN 42 Pidie.